Relationship between glutathione S-transferase M1 gene polymorphism and gastric cancer: baijiaochui07143@163.com - Qi, Ming; Liu, Dongmei; Wang, Hailing; Bianba, Ciren; Ji, Wei (Cellular and Molecular Biology, 2022)
This experiment was designed to investigate the relationship between glutathione S-transferase M1 (GSTM1) gene polymorphism and gastric cancer (GC). For this purpose, from January 2013 to December 2014, 116 patients with GC diagnosed in the Department of Gastroenterology of our hospital and 120 healthy people in the physical examination center were selected as the research objects. 116 patients with GC served as the observation group and 120 healthy people in the physical examination center served as the control group. Collect and isolate the peripheral blood nucleated cells of the subjects, obtain the GSTM1 gene polymorphism by sequencing, analyze the differences of GSTM1 genotype between the two groups, compare the differences of clinicopathological characteristics of patients with different genotypes in the observation group, look for the survival relative risk factors of patients with GC, and analyze the risk factors of death risk of GC by multivariate Cox risk proportional regression. Results showed that the proportion of GSTM1 (-) in the observation group (62.07%) was raised compared with the control group (48.33%) (p<0.05). There was a correlation between GSTM1 gene polymorphism and smoking, TNM stage differentiation and GSTM1 gene polymorphism in the observation group. The specific analysis found that the proportion of non-smoking, stage I-III and low differentiation in the GSTM1 (-) group was raised compared with that in the GSTM1 (+) group (p<0.05). TNM stage, differentiation degree and GSTM1 gene polymorphism were correlated with the median survival time of patients with GC (p<0.05). Further multivariate Cox risk proportional regression analysis showed that TNM stage IV, low differentiation and GSTM1 (-) the relative risk coefficients of death in patients with GC were stage Ⅰ - Ⅲ, high/medium differentiation and GSTM1, respectively (+) patients were 1.75, 1.46, and 2.14 times higher. In conclusion, GSTM1 gene polymorphism is associated with susceptibility to GC, and the GSTM1 deletion genotype is an unfavourable factor for poor prognosis in patients with GC.